2018
DOI: 10.1177/0164027517752149
|View full text |Cite
|
Sign up to set email alerts
|

Lifesaving in Every Way: The Role of Companion Animals in the Lives of Older Lesbian, Gay, Bisexual, and Transgender Adults Age 50 and Over

Abstract: This study uses mixed-methods data and a life-course perspective to explore the role of pets in the lives of lesbian, gay, bisexual, and transgender (LGBT) adults age 50 and over and addresses the following research questions: (1) How does having a pet relate to perceived social support and social network size? and (2) how do LGBT older adults describe the meaning of pets in their lives? The qualitative data (N = 59) were collected from face-to-face interviews, and the quantitative data (N = 2,560) were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 44 publications
1
20
0
1
Order By: Relevance
“…Several qualitative studies have investigated the impact of pet ownership among LGBTQ+ older adult samples and provide evidence that companion animals serve as sources of unconditional love, emotional comfort, and belongingness [45][46][47]. A quantitative study conducted by Muraco et al [48] found that pet-owning LGBTQ+ older adults reported significantly higher perceived social support than LGBTQ+ older adults without pets. However, less is known about the role of companion animals in the lives of younger LGBTQ+ populations and the potential protective impact of relationships with companion animals on experiences of LGBTQ-related stressors.…”
Section: Relationships With Companion Animals As a Protective Factormentioning
confidence: 99%
“…Several qualitative studies have investigated the impact of pet ownership among LGBTQ+ older adult samples and provide evidence that companion animals serve as sources of unconditional love, emotional comfort, and belongingness [45][46][47]. A quantitative study conducted by Muraco et al [48] found that pet-owning LGBTQ+ older adults reported significantly higher perceived social support than LGBTQ+ older adults without pets. However, less is known about the role of companion animals in the lives of younger LGBTQ+ populations and the potential protective impact of relationships with companion animals on experiences of LGBTQ-related stressors.…”
Section: Relationships With Companion Animals As a Protective Factormentioning
confidence: 99%
“…Our results highlighted that sexual minority women were more likely report pet ownership. Muraco et al. (2018) suggested that women might be more likely to be pet owners due to a greater need for companionship and for support during difficult life events.…”
Section: Discussionmentioning
confidence: 99%
“…Engagement with social care networks (i.e., webs of individuals providing emotional and physical assistance; Hughes & Kentlyn, 2011) has also been shown to play a role in promoting positive aging experiences for LGBTQ+ older adults (Erosheva, Kim, Emlet, & Fredriksen-Goldsen, 2016). Recent data also highlight the importance of companion animals, such that LGBTQ+ older adults who own companion animals show high levels of perceived social support (Muraco, Putney, Shiu, & Fredriksen-Goldsen, 2018).…”
mentioning
confidence: 99%
“…There is also growing appreciation of the ways that human-animal relations can have profound benefits to older people's health and wellbeing (Gee and Mueller, 2019). For older LGBTQ people, they can provide nonjudgemental attachment that helps to combat feelings of loneliness and isolation (Muraco et al, 2018).…”
Section: Introductionmentioning
confidence: 99%